"Mein Herze schwimmt im Blut": die Solokantate BW 199 von J.S. Bach als individuelles Klagelied in der Tradition der alttestamentlichen Klagepsalmen - Lescow, Theodor (Biblische Notizen, 2004)
The psalms of complaint in the Hebrew Bible generally fall into three phases: complaint – request for help – affirmation of trust. Between the request and affirmation there is a break, which has been thought to point toward a priestly oracle of salvation (Heilsorakel). Today, this assumption is increasingly doubted. Despite the 2000 year interval and the completely different context of the prayer, cantata BW 199 is structured according to the same principle. This goes to prove that we are dealing here with a selfcontained, elementary prayer structure on which the process of prayer is based.